THE ROMANTICISM OF NOVALIS AS AN APPLICATION TO BUSINESS ADMINISTRATION - de Souza, Guilherme Alberti (Seven Editora, 2025)
This article proposes an approximation between Novalis’ philosophical romanticism and the practice of Business Administration, focusing on the valorization of subjectivity and human relations. It is based on the observation that the classical administrative models, anchored in empiricist rationalism, neglect essential aspects of human existence by objectifying the employee through metrics and data. From the phenomenological and romantic critique, the study presents Novalis’ Ordo Inversus as an ethical and anthropological proposal that repositions the human being at the center of organizational practices. Concepts such as galvanization, interiority, welcoming, and imagination are highlighted as foundations for a more sensitive, integrative, and creative management. In the end, it is argued that Management should be reconceived not only as a technique, but as a science of relationships and presence, capable of revitalizing the corporate environment and rescuing the existential meaning of work. DOI: https://doi.org/10.56238/sevened2025.029-069